Menguji Ketepatan Penambahan Kewenangan Penjabat Melalui Surat Edaran Menteri Dalam Negeri - Catur Agil Pamungkas; Anom Wahyu Asmorojati (Universitas Muhammadiyah Yogyakarta, 2023)
A total of 271 Acting will fill the position of Regional Head for a long time, however Acting has limited authority, one of which is in the staffing aspect where Acting is prohibited from transferring employees without the approval of the Minister of Home Affairs. Based on the principles of effectiveness and efficiency, the Minister of Home Affairs issues a circular letter giving written approval to officials to manage personnel under higher regulations. The purpose of this research is look first at the position of the Circular Letters based on the legal system in Indonesia, secondly, to find out the accuracy of adding the Acting authority through a Circular Letter on the legal system in Indonesia. This research is included in normative legal research with the research approach used, namely the statutory and conceptual approach. This research utilizes primary, secondary, and tertiary legal materials and the collection is carried out by means of a literature study. The result showed that, first, Circular Letters are part of policy regulations that function as an instrument of communication between State Administration positions. Circular Letters are also a manifestation of written discretion not being part of statutory regulations. Second, that the Minister of Home Affairs has exceeded his authority by establishing a new legal norm through a Circular Letter. Where the main substance of the Circular Letter provides written approval to Acting Governors, Regents and Mayors in the aspect of staffing, where this is contrary to higher regulations.